Implementasi e-KTP Dalam Penataan Sistem Administrasi Kependudukan; Studi Kasus di Kota Cimahi - Fitria, Rizky; AndariÂ , Rosita Novi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2012)
e-ID policy, is national strategic programs that applied in 497 districts in Indonesia, where Cimahi has been one of the pilot project area that implemented e-ID in 2011. The purpose of this study is to analyze the extent of implementation e-ID in Cimahi by exploring the opportunity, obstacle through the whole process; therefore it can be formulated into an appropriate strategy implementation to be applied in the regional area. Using qualitative method and data collection techniques with desk research and field research. The result show that e-ID implementation that was held for two periods (October - December 2011 and December 2011 - February 2012 with extension until May 2012) has some obstacles such as as lack of equipment but also generate some opportunities such as good planning, standard operating procedures, coordinating, monitoring, community participate and so on. Cimahi's Government have quite good initiative, creativity and innovation through the process of interpretation, application and monitoring, so some emerging obstacle can be overcome easily. Therefore, the provision of e-ID services in Cimahi can be consider as best practice for other district that currently or planning to implementing the e-ID policy.